Analisis Kebutuhan Pengetahuan Keselamatan dan Kesehatan Kerja (K3) Terhadap Siswa Praktik Kerja Industri di SMK Negeri 1 Kaidipang - Sri Astuti Binol; Hasmah; Frice L. Desei (Jurnal Teknik, 2019)
This research aims to analyze the knowledge necessity and implementation of the occupational health and safety (OHS) of students in SMK Negeri 1 Kaidipang while taking the industrial work practice. This is a quantitative research by applying questionnaires and observation with 2 variables, those are; 1) the knowledge necessity of the occupational health and safety (X) and 2) the implementation of the occupational health and safety in the industrial work practice (Y)..The test with the significance level (a) of 5%. It shows that: (1) Knowledge necessity of occupational health and safety greatly influences its implementation during the industrial work practices, this is evidenced by the R Square value of 0.358 or 35.8% which means that the knowledge necessity of the occupational health and safety variable only contributes 35.8% to its implementation during the industrial work practices. (2) the knowledge necesssity of the OHS positively influences its implementation during the industrial work practice of students in class XI and XII majoring in Architecture with proof of value, count> cable (4,604> 2.02439). The knowledge necessity of occupational health and safety can affect students' awareness in its implementation because students can know the consequences of not paying attention to occupational health and safety